Information network on Twitter regarding early warning of mount Semeru eruption - Bakry, Gema Nusantara; Nurislaminingsih, Rizki (Jurnal Kajian Komunikasi, 2023)
Background: Indonesia is a country that is highly susceptible to volcanic disasters. One potential measure the community can take is to utilize social media platforms to participate in disaster mitigation efforts. The hashtag #Semeru exemplifies the utilization of social media in disseminating information regarding volcanic disasters. It became a trending topic on Twitter regarding the information on the eruption of Mount Semeru at the end of 2021. Purpose: The primary objective of this research is to examine the operational mechanisms of the Mount Semeru eruption early warning system on Twitter. Furthermore, the objective is to determine the key actors responsible for disseminating early warning information on Twitter. Methods: This study employed the Social Network Analysis (SNA) method. Results: The findings show that the network distribution pattern of the Semeru eruption early warning system has a radial communication network pattern with indicators of low network density levels. The actors @fiersabesari, @bnonews, @asumsico, @disclose.tv, @jawafess, and @insiderpaper have a proximity centrality value of 0 due to their lack of acquaintance. On the other hand, two actors possess a closeness centrality value: @melodiysore with a value of 0.8 and @daryonoBMKG with a value of 0.2. This study highlighted that the actors involved in disaster management and mitigation had a level of popularity that ranked outside the top 10. Conclusions: The information network system for the early warning of the Mount Semeru eruption on Twitter forms a network distribution with a radial communication pattern that is concentrated at one point and acts as a key actor. Eight key actors play a role in disseminating early warning messages, specifically @fiersabesari, @daryonoBMKG, @bnonews, @asumsico, @disclose.tv, @theinsiderpaper, @melodiysore, and @jawafess (community). Implications: This study demonstrates the benefits of using Twitter as a timely indicator for disasters, notably the eruption of Mount Semeru. It can effectively engage the community and government in disseminating early-warning information about volcanic eruptions.